INVESTIGATING THE ROOT CAUSES OF LOW ENGLISH-SPEAKING PERFORMANCE: A CASE STUDY AT ENGLISH EDUCATION DEPARTMENT OF MANDALIKA UNIVERSITY OF EDUCATION - Sri Ariani (Sinar Lima, 2025)
This study aims to investigate the root causes of low English-speaking performance among students at the English Education Department of Mandalika University of Education. Despite years of formal instruction, many students still face significant challenges in achieving oral fluency and accuracy. This research employed a qualitative case study approach to gain an in-depth understanding of the phenomenon. Data were collected through semi-structured interviews, classroom observations, and questionnaires involving a selected group of students and speaking lecturers. The findings reveal that the low speaking performance is attributed to a complex interplay of internal and external factors. Internally, psychological barriers such as high levels of anxiety, fear of making grammatical errors, and a lack of self-confidence significantly hinder students' willingness to communicate. Externally, the lack of a supportive English-speaking environment outside the classroom, limited opportunities for authentic interaction, and traditional teaching methods that overemphasize rote memorization of grammar rules contribute to the problem. Furthermore, linguistic issues, particularly limited vocabulary and poor pronunciation, remain primary obstacles. This study concludes that addressing low speaking performance requires a holistic approach, including the implementation of more communicative and interactive teaching strategies, the creation of an English-speaking zone on campus, and the integration of psychological support to build students' confidence. These findings provide valuable insights for curriculum designers and lecturers at Mandalika University of Education to enhance the quality of English-speaking instruction.